Microstructure and ion-exchange properties of transparent glass-ceramics containing Zn2TiO4/α-Zn2SiO4 nanocrystals. Issue 8 (July 2022) - Wang, Sihao; Guo, Yunlan; Lu, Yadong; Liu, Chao; Deng, Zhao; Han, Na; Cui, Jiedong
Abstract: Transparent glass-ceramics have particular properties compared with their precursor glasses, and have promising potential applications in many fields. Titanium-relative phases are frequently employed as nucleation agents for crystallization of glass-ceramics, and rarely been precipitated as functional nanocrystalline phases in glass-ceramics. In this work, transparent glass-ceramics containing Zn2 TiO4 and/or α-Zn2 SiO4 nanocrystals are investigated. It turns out that Vickers hardness of these glass-ceramics increases with the precipitation of Zn2 TiO4 and α-Zn2 SiO4 nanocrystals. Despite the blocking effect of nanocrystals precipitated in the glass-ceramics, structural and compositional modification of the residual glass induced by the precipitation of these nanocrystalline phases facilitates the K-Na ion-exchange, leading to the enhanced depth of layer and further improved Vickers hardness of the glass-ceramics.